A novel HLA allele, HLA‐DQB1*02:57, was identified by polymerase chain reaction sequence‐based typing in a Chinese individual. Issue 3 (3rd August 2015) - Dai, B.; He, J.; Zhu, F.‐M.; Lv, H.‐J.
<x xml:space="preserve">Abstract</x> HLA‐DQB1*02:57 has one base substitution at position 260 T>C in exon 2 from HLA‐DQB1*02:01:01.